Desain Turunan Senyawa Leonurine Sebagai Kandidat Obat Anti Inflamasi : Design of Leonurine Derivatives as Anti-Inflammatory Candidates - Beny, Ruslin; Yana, Nindy Rachma Az; Leorita, Mesi (Universitas Tadulako, 2020)
In this research, there was docking process of leonurine compounds and their derivatives to Cyclooxygenase-2 (COX-2) enzyme as an anti-inflammatory. The receptor code used is 6COX which is downloaded from the protein data bank site (PDB). The aims of this study was to investigate the interaction of leonurine compounds and their derivatives against COX-2 receptors. All compounds are docked using AutoDock 4.2 software. The docking validation is performed by tethering the ligand-receptor with the parameter of the Root Mean Square Deviation (RMSD) value <2 Ã…. From the docking validation results, have been obtained RMSD value = 0.31 Ã…. Analysis of docking results indicates that leonurine and its derivatives are predicted to have good interaction with COX-2 receptors. From the results of this research, it can be concluded that leonurine compounds and their derivatives have inhibitory activity against COX-2 receptors. The docking results showed the lowest binding energy value ligand-receptor (Î”G) best matched in the 11th derived compound which is -7.95 kcal/mol.